1998
DOI: 10.1074/jbc.273.16.9369
|View full text |Cite
|
Sign up to set email alerts
|

Urea Transporter UT3 Functions as an Efficient Water Channel

Abstract: A family of molecular urea transporters (UTs) has been identified whose members appear to have an exceptionally high transport turnover rate. To test the hypothesis that urea transport involves passage through an aqueous channel, osmotic water permeability was measured in Xenopus oocytes expressing UTs. The UT3 class of urea transporters functioned as efficient water channels. Quantitative measurement of single channel water permeability ( p f ) using epitopetagged rat UTs gave p f (in cm 3 /s ؋ 10 ؊14 ) of 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0
8

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(67 citation statements)
references
References 30 publications
5
54
0
8
Order By: Relevance
“…However, UTB inh -14 inhibited water transport significantly in AQP1-null erythrocytes (Figure 5B, right), supporting our prior conclusion that erythrocyte water transport is mediated, in part, by UT-B. 22,27 Figure 5C shows no significant inhibition of CFTR or TMEM16A chloride conductance by 10 mM UTB inh -14, as measured by short-circuit current. Last, by MTT assay, incubation of MDCK cells with UTB inh -14 up to 10 mM for 24 hours (where it remains soluble) showed no cytotoxicity ( Figure 5D).…”
Section: Ut-b Inhibition Mechanism and Specificitysupporting
confidence: 69%
“…However, UTB inh -14 inhibited water transport significantly in AQP1-null erythrocytes (Figure 5B, right), supporting our prior conclusion that erythrocyte water transport is mediated, in part, by UT-B. 22,27 Figure 5C shows no significant inhibition of CFTR or TMEM16A chloride conductance by 10 mM UTB inh -14, as measured by short-circuit current. Last, by MTT assay, incubation of MDCK cells with UTB inh -14 up to 10 mM for 24 hours (where it remains soluble) showed no cytotoxicity ( Figure 5D).…”
Section: Ut-b Inhibition Mechanism and Specificitysupporting
confidence: 69%
“…Urea permeability in erythrocytes from null mice was 45-fold lower than that from wild-type mice, indicating that UT-B was functionally deleted. We found previously that rat UT-B transported some water along with urea when heterologously expressed in Xenopus oocytes (21). Mouse UT-B also functioned as a weak water channel and an efficient urea transporter in Xenopus oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…5Ј and 3Ј end cDNA sequences were obtained by 5Ј-and 3Ј-RACE (CLONTECH). For functional measurements of urea and water permeability, the mouse UT-B cDNA (full-length coding sequence) was subcloned into oocyte expression plasmid pSP64T, and in vitro transcribed cRNA (5 ng) was expressed in Xenopus laevis oocytes as described previously (21). The structure of the mouse UT-B gene was analyzed by PCR amplification of exon-intron-exon fragments by using C57/bl6 mouse liver genomic DNA as template.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two-way ANOVA revealed that there were no Loo et al (1996Loo et al ( , 1999Loo et al ( , 2002, Yang & Verkman (1998 Fig. 1).…”
Section: Phloridzin-treated Cellsmentioning
confidence: 99%